2014
DOI: 10.1155/2014/239495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ExperimentalSarcocystis neurona-Induced Infection on Immunity in an Equine Model

Abstract: Sarcocystis neurona is the most common cause of Equine Protozoal Myeloencephalitis (EPM), affecting 0.5–1% horses in the United States during their lifetimes. The objective of this study was to evaluate the equine immune responses in an experimentally induced Sarcocystis neurona infection model. Neurologic parameters were recorded prior to and throughout the 70-day study by blinded investigators. Recombinant SnSAG1 ELISA for serum and CSF were used to confirm and track disease progression. All experimentally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…We found that equine B lymphocytes express TLR4 on their cell surface but these cells are not responsive to LPS in culture, similar to results seen in humans (Hornung et al, 2002;Wagner, 2004). PWM was chosen as a positive control for this study as it acts independently of TLR4 in humans (Bekeredjian-Ding et al, 2005) and has previously been shown to activate equine B lymphocytes (Lewis, 2014). For each horse sampled in this study, culture for 24 h resulted in no significant TLR4 expression change between unstimulated samples and those stimulated with LPS or PWM.…”
Section: Discussionsupporting
confidence: 63%
“…We found that equine B lymphocytes express TLR4 on their cell surface but these cells are not responsive to LPS in culture, similar to results seen in humans (Hornung et al, 2002;Wagner, 2004). PWM was chosen as a positive control for this study as it acts independently of TLR4 in humans (Bekeredjian-Ding et al, 2005) and has previously been shown to activate equine B lymphocytes (Lewis, 2014). For each horse sampled in this study, culture for 24 h resulted in no significant TLR4 expression change between unstimulated samples and those stimulated with LPS or PWM.…”
Section: Discussionsupporting
confidence: 63%
“…Performance and shipping have been shown to be risk factors for EPM . Other studies have demonstrated that some EPM‐affected horses have decreased immune responses, including decreased antigen‐specific proliferation, as well as increased interleukin‐4 (IL‐4) and decreased interferon‐gamma (IFN‐γ) expression, supporting a cluster of differentiation 4 (CD4) T helper 2 (Th2) response . Additional studies in mice in have supported a role for CD4 Th1 CD8 IFN‐γ in protection because immunocompetent mice develop CD4 and CD8 memory responses, whereas IFN‐γ knockout (KO) and CD8 KO mice develop disease .…”
Section: Introductionmentioning
confidence: 99%
“…The reason for high exposure rates but relatively low morbidity remains unclear as does the life cycle of the parasite in the aberrant horse host. Previous studies indicate a potential aberrant immune response to S. neurona in susceptible horses (Spencer et al, 2004;Scott et al, 2005;Yang et al, 2006;Lewis et al, 2014), indicating EPM susceptibility may persist for the life of the animal and is not a onetime occurrence. Clinical treatment consists of the use of anti-protozoal drugs such as ponazuril, diclazuril, and sulfa drugs as well as corticosteroids to combat associated inflammation (Reed et al, 2016).…”
mentioning
confidence: 99%
“…Whether the horses responding to treatment or are relapsing from their initial infection (i.e., persistent infection) or from re-exposure to the environmental stages of S. neurona is not fully understood (MacKay et al, 2006). Challenges of using the horse to study EPM are numerous and include the complexity of experimental infection, the terminal end-point nature of many studies, and the difficulty in controlling environmental factors (Saville et al, 2001;Witonsky et al, 2008;Lewis et al, 2014). Alternatively, immune compromised, C57bl/6J or BALB/c interferon gamma gene knockout (Ifnc À/À ) mice offer a regularly utilized model for addressing certain aspects of S. neurona pathology (Dubey and Lindsay, 1998;Dubey et al, 2001;Witonsky et al, 2003).…”
mentioning
confidence: 99%